Pendampingan Pembelajaran Melalui Pendekatan Deep Learning dan Literasi Digital dengan Dukungan Teknologi dan Psikologi Pendidikan - Ria Triayomi; Petrus Murwanto; Stefanus Setyo Wibagso; Ongko Handoko; Agnes Fibriana Kurniawati (LP4MK STKIP PGRI Lubuklinggau, 2025)
This community service program aims to support increasing the capacity of teachers at SD Negeri 124 Palembang in implementing deep learning approach to the learning process, as well as strengthening digital literacy and educational psychology. The program is carried out to provide support to schools because they have never joined socialization and workshop regarding the implementation of deep learning approach, also teachers still have limited understanding of the concept of deep learning, the use of technology and the application of educational psychology. The program activities include interactive socialization, practice in preparing teaching modules, and assignments. The results of the program show a significant increase in teachers' knowledge and abilities related to learning process through deep learning approach, the use of technology and application of educational psychology to design innovative learning.